V. I. Lenin and the Socialist Culture - Repšys, Jonas (Problemos, 1970)
The author works out – on the basis of Marxist methodology and Leninist principles of continuity and interrelation of the socialist and bourgeois cultures – some aspects of the further development of the socialist culture. When dealing with the problem the author touches upon such questions as the class character of spiritual culture, its connection with ideology and present-day ideological struggle.